VAR INTERPRETATIONS OF HAAVELMO'S MARKET MODEL OF CAPITAL AND INVESTMENT. (27th June 2014) - Biørn, Erik
<x content-type="archive" xml:space="preserve">Abstract</x> In the paper attempts are made to integrate two parts of Trygve Haavelmo's work: investment theory and dynamic econometric models of interrelated markets. Specifically, the duality in the representation of the capital service price and the capital quantity in relation to the investment price and quantity are brought to the forefront and confronted with elements from simultaneous equation modeling of vector autoregressive systems containing exogenous variables (VARX), using linear four-equation models. The role of the interest rate and the modeling of the expectation element in the capital service price and the capital's retirement pattern, and their joint effect on the model's investment quantity and price dynamics are discussed. Stability conditions are illustrated by examples. Extensions relaxing geometric decay and ways of accounting for forward-looking behavior, including rational expectations, are outlined. Some remarks on the theory-data confrontation of this kind of model are given.